Sopesando al tercero registral versus el usucapiente: Un enfoque desde el sistema peruano - Santillán García, Patricia (2024)
This article analyses the ownership dispute arising from a third party acquiring a real estate from a person who appeared in the Public Records as the owner but without knowing that the real estate was owned by an adverse possessor. The autor approaches this phenomenon based on the provisions of the Peruvian Registry system and its particularities, critically analyzing various positions on this de facto assumption that have been outlined by various doctrines, to subsequently make a comprehensive interpretation of the existing regulations in our system to finally solve this dispute.